Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.2319/021209-98.1
|View full text |Cite
|
Sign up to set email alerts
|

Functional Occlusal Patterns and Their Relationship to Static Occlusion

Abstract: The hypothesis is rejected. An association exists between dynamic occlusion and different aspects of static occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
44
2
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(61 citation statements)
references
References 24 publications
8
44
2
5
Order By: Relevance
“…Thus, at the position of maximal excursion (3.0 mm), the least number of teeth will be in contact. This was confirmed in several earlier studies, which found a higher prevalence of group function occlusion during earlier stages of excursion and a greater prevalence of canine-guided occlusion at maximal excursion (8,24,25).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Thus, at the position of maximal excursion (3.0 mm), the least number of teeth will be in contact. This was confirmed in several earlier studies, which found a higher prevalence of group function occlusion during earlier stages of excursion and a greater prevalence of canine-guided occlusion at maximal excursion (8,24,25).…”
Section: Discussionsupporting
confidence: 77%
“…The inverse relationship between contact number and magnitude of excursion accords with several earlier reports (8,(23)(24)(25). At earlier stages of excursion, many teeth will still be in contact because of the "freedom in centric occlusion" that is naturally present (5,26).…”
Section: Discussionsupporting
confidence: 71%
“…In our study, group guided occlusion was more frequently found in Angle's class III (57%), then class I (51%) and least in class II (25%) which is comparable to other studies. 1 Asawaworarit 12 reported group guidance as predominant occlusal pattern in Thai individuals. Similarly another study reported both group and canine.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior guidance is divided into canine guided, group guided and balanced occlusal scheme. 1 In canine guided occlusion, the overlap of maxillary and mandibular canines results in disengagement of maxillary and mandibular posterior teeth during excursive movement of mandible whereas group guided occlusion results in multiple contacts of maxillary and mandibular teeth on working side during lateral movement of mandible. Although there is no evidence to suggest which type of occlusion should be taken into account yet canine guided is preferred over group function.…”
Section: Introductionmentioning
confidence: 99%
“…4,5) 또한 많은 연구에서 견치 유도를 선호하지만 임상적인 치료 시 어떤 측방 유도가 좋은 가에 대한 의견일치가 부족하다. A: contact only canines on working side (canine guidance); B: contact of first premolars and second premolars on working side; C: simultaneous contacts of several anterior teeth on the working side; D: simultaneous contacts of several posterior teeth on the working side; E: simultaneous contacts of canines and all posterior teeth from first premolars to second molars on the working side; F: simultaneous contacts of several anterior and posterior teeth on the working side; G: simultaneous contacts of teeth on the working side and on the non-working side …”
mentioning
confidence: 99%